2019
DOI: 10.3389/fpubh.2019.00043
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Intimate Partner Violence During Pregnancy Instrument (IPVPI)

Abstract: Background: Intimate partner violence (IPV) during pregnancy can lead to negative consequences for both the mother and offspring. Although IPV is recognized as a worldwide public health issue, its prevalence is considered to be underestimated because cases are likely underreported, suggesting that there might be unmeasured IPV. The aim of this study was to develop an instrument to detect IPV in pregnant women. Methods: A total of 6,590 women in Aichi prefecture, Japan, who to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
17
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 37 publications
7
17
3
Order By: Relevance
“…In the same way, higher education has been associated with lower levels of IPV which supports the findings in this study (29). Previous research also supports that younger age and poorer financial status were associated with IPV during pregnancy as observed by Doi et al (2019). Another study showed that poverty, lack of education and food security is associated with IPV during and after pregnancy (30,31).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the same way, higher education has been associated with lower levels of IPV which supports the findings in this study (29). Previous research also supports that younger age and poorer financial status were associated with IPV during pregnancy as observed by Doi et al (2019). Another study showed that poverty, lack of education and food security is associated with IPV during and after pregnancy (30,31).…”
Section: Discussionsupporting
confidence: 88%
“…Dramatic evidence shows that nearly one third of women aged 15 years and older have experienced IPV during their lifetime globally, and nearly two-thirds of the women in East Asia have experienced IPV (10). IPV during pregnancy leads to negative consequences not only for the mother but also affects children, general women's health, and the economy (11). It is claimed that the cost of IPV is five percent of the total gross domestic product [GDP] (12).…”
Section: Introductionmentioning
confidence: 99%
“…In the same way, higher education leads to lower IPV which supports the study (28). The study also supports that younger age and poor financial status were associated with IPV during pregnancy as observed by Doi et al (2019). Another study shows that poverty, lack of education and food security lead to IPV during and after pregnancy (29,30).…”
Section: Main Findingssupporting
confidence: 80%
“…IPV during pregnancy leads negative consequences not only the mother but also affects the offspring women's health, and economy (11). It is claimed that the cost of IPV is five percent of the total gross domestic product [GDP] (12).…”
Section: Introductionmentioning
confidence: 99%
“…Our hypothesis was that younger mothers may have much more room to improve crying knowledge through educational intervention, which results in lower prevalence of PDD. In this study, young mothers were defined as mothers aged <25 years rather than limited to teenagers due to the Japanese context (Doi & Fujiwara, 2019; Doi, Fujiwara, & Isumi, 2019), that is, maternal age is increasing (the average maternal age at first birth was 25.7‐years old in 1975 and 30.7‐years old in 2015 [Ministry of Health, Labor, and Welfare, 2019]). Among 918,397 births in 2018, teen mothers were only 0.95% whereas mothers aged 24 or less were 9.3% (Ministry of Health, Labor, and Welfare, 2019).…”
Section: Introductionmentioning
confidence: 99%